Simulation and Study of PEMFC System Directly Fueled by Ammonia Decomposition Gas - Zhao, Jian Feng; Liang, Qian Chao; Liang, Yi Fan (Frontiers in Energy Research, 2022)
Ammonia can be stored as a liquid under relatively easy conditions (Ambient temperature by applying 10 bar or Ambient pressure with the temperature of 239K). At the same time, liquid ammonia has a high hydrogen storage density and is, therefore, a particularly promising carrier for hydrogen storage. At the same time, the current large-scale industrial synthesis of ammonia has long been mature, and in the future, it will be possible to achieve a zero-emission ammonia regeneration cycle system by replacing existing energy sources with renewable ones. Ammonia does not contain carbon, and its use in fuel cells can avoid NOx production during energy release. high temperature solid oxide fuel cells can be directly fueled by ammonia and obtain good output characteristics, but the challenges inherent in high temperature solid oxide fuel cells greatly limit the implementation of this option. Whereas PEMFC has gained initial commercial use, however, for PEMFC, ammonia is a toxic gas, so the general practice is to convert ammonia to pure hydrogen. Ammonia to hydrogen requires decomposition under high temperature and purification, which increases the complexity of the fuel system. In contrast, PEMFC that can use ammonia decomposition gas directly can simplify the fuel system, and this option has already obtained preliminary experimental validation studies. The energy efficiency of the system obtained from the preliminary validation experiments is only 34-36%, which is much lower than expected. Therefore, this paper establishes a simulation model of PEMFC directly using ammonia decomposition gas as fuel to study the maximum efficiency of the system and the effect of the change of system parameters on the efficiency, and the results show that the system efficiency can reach up to 45% under the condition of considering certain heat loss. Increasing the ammonia decomposition reaction temperature decreases the system efficiency, but the effect is small, and the system efficiency can reach 44% even at a temperature of 850°C. The results of the study can provide a reference for a more scientific and quantitative assessment of the potential value of direct ammonia decomposition gas-fueled PEMFC.